Isotopic investigations of Chinese ceramics - Henderson, Julian; Ma, Hongjiao; Cui, Jianfeng; Ma, Renjie; Xiao, Hongyan (Springer Nature, 2020)
This chapter provides insights into Chinese ceramic technologies of both bodies and glazes as well as provenance by using isotopes applied to a number of case studies. The use of Sr isotopes to investigate Chinese high-fired Celadon wares and blue-and-white Jingdezhen porcelain (Jiangxi province) has revealed a clear distinction associated with the fluxes used in the glazes: plant ash in celadons and limestone in Jingdezhen glazes, something that is not clear from major element analysis. Furthermore, the technique is able to suggest by implication the nature of the silica source used in the glazes—normally weathered granitic rocks or metamorphic rocks (porcelain stone) which also contains Sr. This leads to an isotopic mixing line of the 2 Sr-rich components and is proof that 2 Sr-rich components were mixed in the manufacture of limestone glaze. This is not the case for plant ash glazes. Eventually, the technique may be used in provenance studies. Like Sr isotope analysis, lead isotope analysis relies on there being a lack of or a minimal change in the isotope ratios when the raw materials are heated. Lead isotope analysis links the use of lead in glazes to the original metal ore and if a kiln uses a distinctive lead source in its glazes, it can provide a provenance for the pottery. This has been very successful in distinguishing Chinese Tang sancai wares made in the Huangye, Huangbao, Liquanfang and Qionglai kilns.